HERBAL REMEDIES AND CONVENTIONAL THERAPIES FOR ENDOMETRIOSIS: A STUDY ON PAIN RELIEF AND ECONOMIC BENEFITS IN EGYPT - Waleed Ahmad Ali Hussein Atteia, Ahmed Abdelkader Ahmed, Ahmed Omar Mahmoud, Hisham Ahmed Abou-Taleb, Norhan Y. A. Hussein (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Background: Endometriosis is a chronic inflammatory condition characterized by the growth of endometrial-like tissue outside the uterus, affecting approximately 10% of women in the reproductive age range. It is commonly associated with debilitating pain, including dysmenorrhea, chronic pelvic pain, and dyspareunia. Current treatments, including NSAIDs, hormonal therapies, and GnRH analogs, often fail to provide adequate relief or are associated with intolerable side effects. As a result, many patients turn to complementary therapies, including the use of medicinal and aromatic plants (MAPs), which are valued for their anti inflammatory and analgesic properties. However, there is limited empirical data on the effectiveness and safety of these therapies.